Greater Mekong subregion atlas of the environment (Asian Development Bank, 2012)
This book includes many parts: greater Mekong subregional profile, peoples of the Greater Mekong subregion, environmental and natural resources, development in the Greater Mekong subregion, challenges and responses, information resources.